5. Important Mycotic Diseases In Animal Livestock Caused By Some Agriculture Fungi In Indonesia - Riza Zainuddin Ahmad; Djaenudin Gholib (The International Journal of Tropical Veterinary and Biomedical Research, 2016)
One of contribution for Indonesian state from Agriculture sector is livestock animals. This livestock animals in Indonesia is divided to large and small ruminant, poultry, and other commercial animals. All these animals can be infected by some agriculture fungi which causes mycosis. The disease cause economic loss by morbidity and mortality. In chicken (poultry), aspergillosis caused by Aspergillus sp can be very important among mycotic diseases. In ruminant ringworm (dermatofitosis) caused by dermatofit fungi which infected skin, and mastitis caused by fungi in Dairy cattle causes decrease milk production. Histoplasmosis caused by fungi such as Histoplasma farciminosum is called Selakarang, infect horse. This paper discribes these mycotic diseases and control and to give more information of fungal disease caused by some agriculture fungi.